Determination of 2-methoxyphenol in model solutions by spectrophotometry; Modern Analytical Chemistry - Alikova V. D. Valeriya Dmitrievna; Chernova A. P. Anna Pavlovna; Shormanov V. K. Vladimir Kambulatovich; Korotkova E. I. Elena Ivanovna (2020, 2020)
Title screen